Pengaruh Customer Relationship Management (Crm) Terhadap Loyalitas Pengguna Irian Card (I-Card) Pada Irian Dept Store & Supermarket Medan Marelan - Dinanti Nanda Pertiwi; Winda Cahyani; Ari Usman Chaniago (STMIK KAPUTAMA, 2020)
This study discusses the influence of Customer Relationship Management which consists of 5 variables: commitment, trust, customer orientation / empathy, experience / satisfaction, and communication to customer loyalty. To find out whether the 5 Customer Relationship Management variables significantly affect customer loyalty, either partially or simultaneously, and to find out which variable has the most dominant influence on customer loyalty. This research was conducted at Irian Dept. Store & Supermarket Medan Marelan, with the study population being consumers who shop at Irian Dept. Store & Supermarket Medan Marelan with a total sample of 30 respondents. Data collection was carried out through a questionnaire. Furthermore, the data obtained were analyzed using the validity test, reliability test, multiple linear regression analysis, t test, and F test. The results of the calculation of the coefficient of determination (R2) amounted to 0.866, which means; the 5 customer relationship marketing variables affect the loyalty variable of 886.6%.